A Model for Funding Interrelated Research and Development Projects under Uncertainty - Aldrich, Carole A. (Journal of Financial and Quantitative Analysis, 1974)
Selection of funding levels for research and development (R & D) projects is a major problem facing the firm. Models for selecting funding levels have frequently been formulated under the assumptions that the projects can be evaluated independently (Aldrich [1], Hess [4], Lucas [6]) or that the projects are interrelated only in terms of requirements for specialized input resources (Asher [2]). In fact, the projects of a given firm are likely to be highly interdependent, either in the sense that progress on one project eases work on another (research interdependency) or in the sense that completion of one project alters the market situation of another (output interdependency). While Weingartner [8] discusses these interdependencies, he does so under the assumption that the project funding level is fixed.